A Toxoplasma gondii patatin-like phospholipase contributes to host cell invasion. - Sarah K Wilson; Justine Heckendorn; Bruno Martorelli Di Genova; Lindsey L Koch; Peggy J Rooney; Naomi Morrissette; Maryse Lebrun; Laura J Knoll (PLoS Pathogens)
Toxoplasma gondii is an obligate intracellular parasite that can invade any nucleated cell of any warm-blooded animal. In a previous screen to identify virulence determinants, disruption of gene TgME49_305140 generated a T. gondii mutant that could not establish a chronic infection in mice. The protein product of TgME49_305140, here named TgPL3, is a 277 kDa protein with a patatin-like phospholipase (PLP) domain and a microtubule binding domain. Antibodies generated against TgPL3 show that it is localized to the apical cap. Using a rapid selection FACS-based CRISPR/Cas-9 method, a TgPL3 deletion strain (ΔTgPL3) was generated. ΔTgPL3 parasites have defects in host cell invasion, which may be caused by reduced rhoptry secretion. We generated complementation clones with either wild type TgPL3 or an active site mutation in the PLP domain by converting the catalytic serine to an alanine, ΔTgPL3::TgPL3S1409A (S1409A). Complementation of ΔTgPL3 with wild type TgPL3 restored all phenotypes, while S1409A did not, suggesting that phospholipase activity is necessary for these phenotypes. ΔTgPL3 and S1409A parasites are also virtually avirulent in vivo but induce a robust antibody response. Vaccination with ΔTgPL3 and S1409A parasites protected mice against subsequent challenge with a lethal dose of Type I T. gondii parasites, making ΔTgPL3 a compelling vaccine candidate. These results demonstrate that TgPL3 has a role in rhoptry secretion, host cell invasion and survival of T. gondii during acute mouse infection.